2018
DOI: 10.1038/s41698-017-0044-8
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C preferentially kills cancer stem cells in hepatocellular carcinoma via SVCT-2

Abstract: Vitamin C (L-ascorbic acid, ascorbate, VC) is a potential chemotherapeutic agent for cancer patients. However, the anti-tumor effects of pharmacologic VC on hepatocellular carcinoma (HCC) and liver cancer stem cells (CSCs) remain to be fully elucidated. Panels of human HCC cell lines as well as HCC patient-derived xenograft (PDX) models were employed to investigate the anti-tumor effects of pharmacologic VC. The use of VC and the risk of HCC recurrence were examined retrospectively in 613 HCC patients who rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
145
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(154 citation statements)
references
References 44 publications
6
145
0
3
Order By: Relevance
“…Therefore, SVCT2 might be implicated in the ascorbate induced cancer cell death phenomena. Similar results were observed by two groups in cholangiocarcinoma cells (Wang et al, 2017), hepatocellular carcinoma (Lv et al, 2018) and colon cancer cells (Cho et al, 2018), where SVCT2 expression determines the susceptibility to pharmacological ascorbate-induced cell death.…”
Section: Vitamin C Transport and Compartmentalization In Cancer Cellssupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, SVCT2 might be implicated in the ascorbate induced cancer cell death phenomena. Similar results were observed by two groups in cholangiocarcinoma cells (Wang et al, 2017), hepatocellular carcinoma (Lv et al, 2018) and colon cancer cells (Cho et al, 2018), where SVCT2 expression determines the susceptibility to pharmacological ascorbate-induced cell death.…”
Section: Vitamin C Transport and Compartmentalization In Cancer Cellssupporting
confidence: 86%
“…Another report performed in 73 patients with acute myeloid leukemia showed that IV ascorbate treatment combined with chemotherapy produced a higher complete remission and prolonged survival compared to patients who received only chemotherapy (Zhao et al, 2018). In a retrospective study in 613 hepatocellular carcinoma patients, it was shown that IV ascorbate administration improved disease-free survival of patients after surgery (Lv et al, 2018). Finally, a phase I metastatic colorectal and gastric cancer study in 36 patients applying high-dose AA in combination with mFOLFOX6 or FOLFIRI, showed potential clinical efficacy in these patients (Wang et al, 2019).…”
Section: Vitamin C Administration In Clinical Studiesmentioning
confidence: 99%
“…Several studies have demonstrated that L-ascorbic acid/VC, in addition to its role in cancer treatment, [35][36][37][38] promotes mammalian cell differentiation and DNA synthesis. 6,27,30,32 However, the impact of VC on the differentiation and effector function of human γδ T cells has not been addressed to date.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies during the past decade confirmed that pharmacological concentrations of Vit.C in the millimolar range are effective in in vitro studies as they kill cancer cells, and in vivo by slowing down the tumor growth [9,98]. However, the mechanism behind the sensitivity of cancer cells to Vit.C and resistance of normal cells to Vit.C is still not clearly understood and needs further investigation.…”
Section: Vitc and Its Anticancer Mechanismmentioning
confidence: 99%